The Same Old New South: Pride or Prejudice? - John Ford (Les Cahiers de Framespa)
This article examines the somewhat perplexing pride that can be shown in the antebellum and Confederate history of the Old South on the one hand, and the celebration of African-American heritage and pride in an integrated New South on the other. It examines how each is celebrated in Atlanta, Georgia, focusing on the way in which the Old South was remembered from the end of the Civil War until the Civil Rights movement a century later – the «Old New South» – and how it has been re-remembered in the period since the Civil Rights movement – the «new New South». While today there is a vibrant pride in the city’s African-American culture, there also remains a healthy degree of pride in the Old South, and most of its adherents do not consider the two movements to be antagonistic. This paper seeks to examine how such a paradox could come about. It also posits reasons for the way in which Old South heritage was intentionally changed to make it acceptable when changing times made it questionable.